Efficacy of Different Commercial Vitamin - Mineral Premixes on Productive Performance of Caged Laying Pullets - Asaduzzaman, M.; Jahan, M.S.; Mondol, M.R.; Islam , M.A.; Sarkar, A.K. (International Journal of Poultry Science, 2005)
A total of ninety-six Shaver 579 pullets were fed on isocaloric and isonitrogenous diet with vitamin-mineral premixes, Supramixes Layer, Acimix Super-L and Adivit-L and without premix (control) in the age duration from 25 to 40 weeks to evaluate the efficacy of different commercial premixes. Daily feed intake and body weight gain of the pullets did not differ significantly (P>0.05). Hen day egg production of different treatments differed significantly (P< 0.01). Higher and statistically similar egg production was obtained in Supramix layer (75.4%) and Acimix Super-L (74.12%) treatment. The lowest (62.5%) and statistically similar (65.99%) egg production occurred in control and Adivit-L treatment respectively. Egg weight of the treatments differed significantly (P< 0.01). The highest (57.15g) and statistically similar (56.57g) egg weight was observed in supramix Layer and Acimix Super-L group respectively. The highest egg mass output of Supramix Layer (42.98) differed significantly (P< 0.01) from the control (33.98). Significant (P< 0.01) difference was observed in the FCR value of Supramix Layer (2.68) and control (3.43) group. Broken egg percent of the treatments differed significantly (P< 0.01). High broken egg (4.11%) was observed in control group. No significant (P>0.05) differences were observed in livability. The observation of the results showed that use of commercial vitamin-mineral premix to supplement the diet of caged laying pullets is inevitable to maintain desirable production level. But the efficacy of all commercial premixes was not equal. The quality of marketed premixes is not uniform which is revealed in terms of performance test in the study.